Linguoevocation research of pedagogical interpersonal communication: based on a fragment of a literary text - Eleanor Malygina (Philology & Human, 2021)
The article is devoted to the problem of linguo-translational research of pedagogical (school) interpersonal communication, reproduced in a fragment of the text of O. Kamaeva's novel " Christmas Tree. From school with love, or The Teacher's Diary." The methodology is based on the parameter of the two-dimensional linguoevocation study of the text. The primary plan is subordinated to the category of evocativeness of a literary text. An important place belongs to the means of reproducing the model of pedagogical communication as a product of evocation. The description of the model of the depicted interpersonal interaction is made according to the parameters of the  verbal communication act proposed by B. Y. Gorodetsky. The secondary plan of studying pedagogical communication is related to the category of interpretativeness of the text. The results of the study, obtained in the course of the linguistic-evocation description of interpersonal communication of the primary plan, allow the reader to see the components of the object of interpretation, to establish the relationship between the problem of the teacher's speech image and the process of effectuating the interaction of characters.